Remediation of antimony-contaminated soil with composite materials of Fe/Fe2+-fly ash-concrete additive in seasonal freezing regions - Jiang, Miao; Wang, Kun; Xue, Ruiyuan; Zhao, Qingliang; Wang, Long; Wang, Weiye; Ding, Jing (Process safety and environmental protection, 2022)
Antimony (Sb) finds its wide application in industries, however, the research on Sb solidification/stabilization (S/S) in the Sb-contaminated soil is currently insufficient, particularly in seasonal freezing regions. Here six composite materials of Fe/Fe2+-fly ash-concrete additive (Fe-FA-CA) were employed and optimized to remediate the Sb-contaminated soil subject to 40 freezing-thawing (F-T) cycles. After remediation, FeSO4-fly ash-calcium lignosulfonate (FFC) exhibited the best resistance performance to F-T. The stabilization efficiency was evaluated with TCLP at 92.92%. Meanwhile, Sb concentration met the criteria of landfill for inert waste assessed with the compliance test for leaching (CT) of European Standard. The S/S efficiency of Sb dropped slightly from 92.68% to 88.22% (TCLP) and from 97.18% to 93.37% (CT), respectively, after aging 40 F-T cycles. The fraction of residual Sb in the soil treated by FFC was increased by 10.41%, and the strength of the S/S soil was much higher than 350 kPa, the requirement of landfills in the U.S. during F-T cycles. Additionally, the poorly crystalline Fe in the soil remediated by FFC was increased by 4.54 g/kg, suppressing Sb migration. The feasibility and effectiveness of FFC in S/S of Sb demonstrated its potential to remediate Sb-contaminated soil in seasonal freezing regions. [Display omitted]